Spirocyclic Amide Acetal Synthesis by [CpRu]‐Catalyzed Condensations of α‐Diazo‐β‐Ketoesters with γ‐Lactams. Issue 10 (7th September 2021) - Pertschi, Romain; Brun, Elodie; de Aguirre, Adiran; Guénée, Laure; Poblador‐Bahamonde, Amalia I.; Lacour, Jérôme
Abstract: The synthesis of spirocyclic amide acetals (33–93 %) has been achieved through Ru(II)‐catalyzed condensations of N ‐carbamate protected pyrrolidinones with metal carbenes derived from α‐diazo‐β‐ketoesters. Thanks to the mildness of the diazo decomposition conditions induced by a 1 : 1 combination of [CpRu(MeCN)3 ][BArF ] and 1, 10‐phenanthroline, the formation of the sensitive products is possible. Full characterization of this carbonyl‐ylide mediated process is provided by DFT calculations. Abstract :